Komunikasi Massa Sebagai Bentuk Pengawasan Terhadap Kebijakan Politik - Kartini Kartini; Novia Elisa; Nurtia Asty Rahman; Adiva Amanda; Nada Hanifah Harahap; Rahmi Hilda Yanti Lubis (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This research was written and packaged to provide information related to mass communication. This article links mass communication to political policy. Mass communication can be used as a medium to monitor policies made by the government. Basically, Indonesia is a democratic country and the people's prosperity will be prioritized. Therefore, to follow up on unfair policies carried out by the government, a forum is needed to be able to correct this. This article will discuss how mass communication can fulfill the function of monitoring political policies. Political policies will also be described in this article, accompanied by an examination of policies that are not appropriate by society. The mass communication model will determine the direction of how this mass communication will run. Mass communication will definitely have the effect of building public awareness and correction towards the government.